Strengthening Grievance Mechanisms in Georgia - World Bank (Washington, DC : World Bank, 2022)
This note offers an overview of challenges and lessons learned from the 2019 effort, then reviews each of the PIU’s GMs, including the respective GM complaint uptake channels, overall GM architecture, registration and categorization processes, investigation and resolution mechanisms, related communication efforts, and grievance-related data. Efforts taken to strengthen the GMs since the 2019 technical assistance until late 2021 are highlighted, and areas for growth are explored. This note is intended for World Bank task teams and PIUs to show how a rapid diagnostic can lead to significant improvements in the design and implementation of GMs and a marked enhancement of social accountability in projects financed by multilateral development banks.